2023
DOI: 10.1002/ptr.7982
|View full text |Cite
|
Sign up to set email alerts
|

Angelica sinensis polysaccharide ameliorates nonalcoholic fatty liver disease via restoring estrogen‐related receptor α expression in liver

Abstract: Angelica sinensis polysaccharide (ASP) showed increasingly recognized hepatoprotective effects and lipid regulation. Because polysaccharides are typically degraded into fragments or short‐chain fatty acids in the gut, rather than being absorbed in their intact form, it is worth pondering why ASP can regulate hepatic lipid metabolism and protect the liver from damage caused by lipid accumulation. In vivo and in vitro nonalcoholic fatty liver disease (NAFLD) models with lipid accumulation were established to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Angelica sinensis polysaccharide (ASP) has garnered significant attention due to its notable hepatoprotective effects. Previous research has demonstrated that ASP exerts therapeutic effects on NAFLD through the regulation of lipid metabolism via the propionate/ERRα pathway ( Luo et al, 2023 ). Furthermore, ASP has the capacity to enhance the expression of PPARγ and key liver insulin signaling proteins, such as IRS-2, PI3K, Akt, p-Akt, and GLUT2.…”
Section: Methodsmentioning
confidence: 99%
“…Angelica sinensis polysaccharide (ASP) has garnered significant attention due to its notable hepatoprotective effects. Previous research has demonstrated that ASP exerts therapeutic effects on NAFLD through the regulation of lipid metabolism via the propionate/ERRα pathway ( Luo et al, 2023 ). Furthermore, ASP has the capacity to enhance the expression of PPARγ and key liver insulin signaling proteins, such as IRS-2, PI3K, Akt, p-Akt, and GLUT2.…”
Section: Methodsmentioning
confidence: 99%